Diagnostic performance of calcification-suppressed coronary CT angiography using rapid kilovolt-switching dual-energy CT. - Yunaga, Hiroto; Ohta, Yasutoshi; Kaetsu, Yasuhiro; Kitao, Shinichiro; Watanabe, Tomomi; Furuse, Yoshiyuki; Yamamoto, Kazuhiro; Ogawa, Toshihide (European Radiology, 2017)
Objectives: Multi-detector-row computed tomography angiography (MDCTA) plays an important role in the assessment of patients with suspected coronary artery disease. However, MDCTA tends to overestimate stenosis in calcified coronary artery lesions. The aim of our study was to evaluate the diagnostic performance of calcification-suppressed material density (MD) images produced by using a single-detector single-source dual-energy computed tomography (ssDECT).Methods: We enrolled 67 patients with suspected or known coronary artery disease who underwent ssDECT with rapid kilovolt-switching (80 and 140 kVp). Coronary artery stenosis was evaluated on the basis of MD images and virtual monochromatic (VM) images. The diagnostic performance of the two methods for detecting coronary artery disease was compared with that of invasive coronary angiography as a reference standard.Results: We evaluated 239 calcified segments. In all the segments, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy for detecting significant stenosis were respectively 88%, 88%, 75%, 95% and 88% for the MD images, 91%, 71%, 56%, 95% and 77% for the VM images. PPV was significantly higher on the MD images than on the VM images (P < 0.0001).Conclusions: Calcification-suppressed MD images improved PPV and diagnostic performance for calcified coronary artery lesions.Key Points: • Computed tomography angiography tends to overestimate stenosis in calcified coronary artery. • Dual-energy CT enables us to suppress calcification of coronary artery lesions. • Calcification-suppressed material density imaging reduces false-positive diagnosis of calcified lesion.